On a Characterization of Convergence in Banach Spaces with a Schauder Basis - Marat V. Markin; Olivia B. Soghomonian (International Journal of Mathematics and Mathematical Sciences)
“The method in the present paper is abstract and is phrased in terms of Banach spaces, linear operators, and so on. This has the advantage of greater simplicity in proof and greater generality in applications.” Jacob T. Schwartz